Spatio And Temporal Dimensions For The Public Usage Of Urban Green Parks In Colombo, Sri Lanka - PGR Naleen Indika Pussella; Lin Li (Indonesian Journal of Tourism and Leisure, 2022)
Use and accessibility to green parks in urban environments by public is an indicator to measure the psychological and physiological sustainability of dwellers. Identifying the driving forces in selecting a park for leisure and discover the pattern of park usage in Colombo city, Sri Lanka were the main objectives of this study. A structured questionnaire was used to collect data from three types of respondents: regular park users who use the nearest park from residence, regular park users who don’t use the nearest park to the residence and non regular park users. Initially, it was selected 2879 participants for this survey representing village administration of Colombo city limits and the questionnaire was returned by 2328 respondents. However, 12 forms were incomplete status, only 2311 responses were selected for further analysis. These respondents were selected randomly to represent each administrative division by considering the total population of them. Statistical Package for Social Sciences (SPSS) application was to analyze the characteristics of park users. It was revealed that nearly a half of the respondents do not use parks regularly and identified a number of characteristics of respondents and reasons for usage and non-usage of green parks regularly. Education, employment, age, civil status and accommodation type were identified as driving forces for the use of parks by general public. Safety and environmental factors were identified as the main issues on selecting parks. Study recommends to policy makers to identify these demerits to take immediate actions to popularize parks among public as an urgent requirement in the urban development and planning processes.